Tinjauan Hukum Terhadap Pemanfaatan Sarang Burung Walet(Collocalia Spp) Di Propinsi Kalimantan Timur - La Sina (Fakultas Hukum Universitas Mulawarman, 2005)
ABSTRACT Most of Collocalia Spp. are included in the species of swallow the family of Collocalia, these bird are available in the province of East Kalimantan. The Collocalia Spp is very useful for increasing the sosial welfare and improving the economy life of the society so that on the advantages of habitat the Collocalia Spp. Is often being the struggling either among the society or the regional government in the case of its management. The provitable of the Collocalia Spp. Is being able to be done only by the one who has got the ringht after having the permit from the regional government. Key words : tinjauan hukum (a study of law), burung walet (collocalia Spp.)